2015
DOI: 10.1002/term.1996
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapy strategy for bile duct repair using tissue engineering technique: PCL/PLGA bilayered scaffold with hMSCs

Abstract: The current clinical treatments for complications caused by hepatobiliary surgery still have some inevitable weakness. The aim of the study was to fabricate a tissue-engineered bile duct that utilized a novel bilayered polymer scaffold combined with human bone marrow-derived mesenchymal stem cells (hMSCs) for new treatment of biliary disease. The biocompatibility of polycaprolactone (PCL) (PCL)/poly(lactide-co-glycolide) (PLGA) scaffold with hMSCs was first examined, and the hMSC-PCL/PLGA constructs (MPPCs) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
1
27
0
2
Order By: Relevance
“…The measured tensile modulus of the multi-layer 3D-fabrication of PLGA/GelMA/IKVAV/USPIO scaffold was in the range of 14.05 -20.37 MPa and the compressive modulus in the range of 0.024 -0.04 MPa, which was suitable for bile duct implantation. Previous research also reported that the mechanical strength of the pure PLGA scaffold was similar to a real bile duct (Zong et al, 2017). The mechanical test indicated that the PLGA/GelMA/IKVAV/USPIO 3D conduit has both flexibility and toughness, which provide a supporting structure and allow duct regeneration.…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 66%
See 2 more Smart Citations
“…The measured tensile modulus of the multi-layer 3D-fabrication of PLGA/GelMA/IKVAV/USPIO scaffold was in the range of 14.05 -20.37 MPa and the compressive modulus in the range of 0.024 -0.04 MPa, which was suitable for bile duct implantation. Previous research also reported that the mechanical strength of the pure PLGA scaffold was similar to a real bile duct (Zong et al, 2017). The mechanical test indicated that the PLGA/GelMA/IKVAV/USPIO 3D conduit has both flexibility and toughness, which provide a supporting structure and allow duct regeneration.…”
Section: Mechanical Properties Of the Scaffoldsmentioning
confidence: 66%
“…Among them, poly (L-lactide-co-glycolide) (PLGA) and polycaprolactone (PCL) was a biocompatible (Reid et al, 2013), degradable (Lee et al, 2012), non-toxic material (Li et al, 2015). It has many successful applications in bile duct regeneration (Zong et al, 2017). PLGA could provide sufficient support strength to prevent bile duct contraction and narrowness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7,8 ] Furthermore, PLGA scaffolds made using conventional methods generally do not support injectability and are only implantable after fabrication, which makes them unsuitable for minimally invasive delivery. [ 6,9 ] There remains a critical need to develop injectable and in situ crosslinkable PLGA scaffolds that are macroporous and support homogeneous cell encapsulation.…”
Section: Figurementioning
confidence: 99%
“…Some polymeric materials have already been proposed as artificial substitutes of both natural and synthetic bile ducts [25,26]. Zong et al focused on the necessity of the scaffold not only being a passive conduit to allow bile flux, but also potentially supporting cell penetration, adhesion, and differentiation, as well as its degradation within the given time [27].…”
mentioning
confidence: 99%